Avoiding granulations and accidental decannulation in paediatric tracheostomy - Munjal, Manish; Munjal, Shubham; Bhatt, Deepak; Arora, Vineeta; Sharma, Salony; Talwar, Shivam; Chawla, Deeksha; Kaur, Hardeep; Sandhu, Lovleen; Arora, Anurima; Bharadwaj, Iti; Joshi, Tanvi (International Journal of Contemporary Pediatrics, 2022)
Tracheal access, accidental deccannulation, peristomal granulation, stenosis and difficult weaning are the laryngologist’s dilemma, wherever tracheostomy has been resorted to, in the paediatric age group. These major problems necessitate a modification in the procedure of tracheostomy where ‘stay’ and ‘maturation’ sutures are utilized. The stay sutures facilitate a quick midline tracheotomy and the maturation ones minimise parastomal granulation and easy tracheal recannulation.